アルツハイマー型認知症高齢者の「食事行為の自立を促す支援プロセス」の検討—作業療法士の食事支援による行為分析から - 濱本 尊博; 藤本 幹 (作業療法, 2024)
要旨：本研究は，認知症高齢者の食事行為の自立を促す作業療法士（以下，OT）のプロセスを明らかにすることを目的に，自立した食事行為に至った経験のあるOTを対象に面接を行い，修正版グラウンデッド・セオリー・アプローチを用い，アルツハイマー型認知症に限定し分析した．その結果，OTは認知症高齢者に対して【その方に合った食事しやすい環境を作る】ことや【気持ちの安定を図る】ようにしていた．この両者の安定が図られたうえで【使える能力を最大限に活かす】取り組みをしていた．認知症高齢者自身を中心とし，その方ができることを尊重しながら，その方に合わせた関わりをすることで自立した食事行為に繋がる要因となることが示唆された. 　The purpose of this study was to elucidate the process of occupational therapists (OT) promoting independence in eating behaviors among older adults with dementia. Interviews were conducted with OT who experienced independent dietary behaviors, using a modified Grounded Theory approach specifically focused on Alzheimer's disease dementia. As a result, OT addressed older adults with dementia who had eating behavior issues by creating an environment conducive to eating that suited the individuals and promoting emotional stability. With these stabilizations in place, they engaged in initiatives to maximize the use of the individuals' capabilities. The study suggests that focusing on older adults with dementia, respecting their abilities, and adapting interactions to their needs can be factors contributing to independent eating behaviors.